Determinan Tingkat Kemiskinan di Indonesia - Afriliya Tri Putri; Dedi Mardianto (Universitas 45 Surabaya, 2025)
This discussion aims to analyze the influence of HDI, unemployment rates, and inflation on poverty in 5 provinces that are categorized as having high poverty rates by using cross section data and time series data for 2012-2023 sourced from the Central Statistics Agency (BPS). The method used is quantitative with a panel data regression analysis approach. The results of this discussion show that percially (t-test) the HDI variable has a significant negative effect while the unemployment rate and inflation variables have no significant effect on poverty in 5 provinces in the highest poverty category. However, simultaneously (test F) the HDI variables, unemployment rate and inflation together have a significant effect on poverty in the 5 provinces that have the highest poverty rate. Therefore, the increase in HDI reduces poverty, so policies must focus on education, health, and welfare. Unemployment and inflation need to be controlled with a comprehensive approach to the effectiveness of poverty alleviation.